“Crying Doesn’t Work”: Emotion and Parental Involvement of Working Class Mothers Raising Children with Developmental Disabilities - Sousa, Amy Christine (Disability Studies Quarterly, 2015)
This article presents three critical case studies that explore the relationship between income and parental involvement in the education of children with developmental disabilities. Interviewed as part of a larger study on mothering children with developmental disabilities, Joy, Jackie, and Maya are low income mothers of children with severe developmental disabilities living in New Hampshire. These women describe carefully planned parenting practices designed to foster child development, which yield both engagement with and strategic disengagement from formal bureaucracies. This is a decided departure from previous theorization on low income mothers' approaches to child development. Grounded analysis of these interview cases suggests that emotion management may be a critical factor in both structuring parental involvement with educational systems as well as enacting class differences within the special education system.